PENGEMBANGAN BUKU AJAR EVALUASI PENDIDIKAN FISIKA BERBASIS PENDEKATAN KONSTRUKTIVISTIK - Nurhayati, Nurhayati; Sukadi, Eti (Universitas Tanjungpura, 2019)
AbstractThis study aims to 1) Produce instructional textbook of physics education based on constructivistic approach, and 2) Knowing the quality of textbooks in terms of feasibility aspects of content, feasibility of presentation, language feasibility and feasibility grafika according to experts. This research is an R & D research with procedural model that adapted the procedure of ADDIE development which consists of three stages: analysis, design, and development. The research instrument is in the form of scale of textbook quality assessment using Likert scale made in the form of checlist. The subjects of textbook quality assessment are three material experts and three media experts. Textbook quality data obtained in the form of quantitative data is converted by product quality percentage scale. The result of this research are: (1) Developed instructional product in the form of textbook based on constructivistic approach as learning material of physics education evaluation in accordance with KKNI curriculum, and (2) The quality of textbook developed has excellent quality (SB) based on assessment of material experts with a percentage of 84.05% of ideal high score 148, and excellent quality (SB) based on media expert's judgment with a percentage of 82.56% of the ideal high score of 80.Keywords: textbooks, physical education evaluations, constructivistically